الإسرائيليات في تفسير البغوي سورة آل عمران، المائدة، الأنعام - زايد, جمعة مسعود (Sharwes Scientific Journal, 2024)
Al-Baghawi’s interpretation, may Allah have mercy on him, is considered one of the important interpretations. Scholars praised his interpretation, relied on it and took care of it, and it gained popularity and spread. Despite what distinguishes Al-Baghawi’s interpretation, it contained many Israeli narrations and false narrations. This was reported from some of the Companions and the Successors and their followers, and some of them were attributed to the Prophet. The Prophet, may God bless him and grant him peace, lied and forged, and all of this has nothing to do with Islam. These false narrations distract people from the purpose for which the Qur’an was revealed and distract them from contemplating its verses and absorbing its lessons and sermons. Therefore, in this research, I wanted to list these Israeli narratives, criticize them, and dispel the lies about the Messenger of God, may God bless him and grant him peace, and his companions.